Shrinkage property of bentonite-sand mixtures as influenced by sand content and water salinity. (10th November 2019) - Zhang, Huyuan; Tan, Yu; Zhu, Fei; He, Dongjin; Zhu, Jianghong
Highlights: 30% is the minimum R S to reduce the shrinkage of PBSMs. Pore water salinity reduces the shrinkage of PBSMs due to bentonite flocculation. Poorly graded GSD reduces the shrinkage of PBSMs. The shrinkage process of PBSMs is a type of packing phenomenon. Abstract: The shrinkage of bentonite-sand mixtures may degrade the performance of a clay barrier constructed in waste disposal facilities. In this study, changes to material properties occurring when bentonite was modified by addition of sand and exposure to different pore water salinities were considered. Paste-like bentonite-sand mixtures were free-desiccated in the laboratory. Sand addition could only reduce the volumetric shrinkage of material when the percentage of sand was larger than 30%. Changes in pore water salinity also may reduce shrinkage of the material because bentonite aggregates were flocculated by synthetic brackish groundwater based on results from particle and pore size analysis. For both effects on the bentonite, the reductions of material shrinkage can be considered theoretically by a packing phenomenon accompanied by the evolution of a mixed grain size distribution.